Pertanggungjawaban Pidana Istri sebagai Pelaku KDRT terhadap Suami Perspektif Hukum Positif dan Hukum Pidana Islam - Fiqhry Al-Faidzin (Jurisprudensi: Jurnal Ilmu Hukum, 2025)
This study examines the criminal liability of wives as perpetrators of domestic violence against their husbands from the perspective of Indonesian positive law and Islamic criminal law (fikih jināyah). The method used is descriptive-analytical qualitative through literature study, regulatory analysis, and secondary data from the 2022–2025 period. The results show that, normatively, fiqh jināyah allows for the punishment of perpetrators of domestic violence through ta‘zīr sanctions without distinguishing between genders, while in positive law, the main basis is Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law) as lex specialis with the Criminal Code as a general reference. However, law enforcement still faces obstacles in the form of stigma against male victims, barriers to reporting, and limited data on cases of wives as perpetrators against their husbands, thus requiring more inclusive and gender-neutral policies.